The path of transboundary marine plastic waste management in China, Japan, and South Korea from the perspective of the blue economy - Hao, Huijuan; Jiang, Chenfan (Frontiers in Marine Science, 2023)
Marine plastic waste is one of the most difficult global ocean governance issues at present, and is also the focus of marine waste governance in the Yellow Sea and East China Sea region surrounded by China, Japan, and Republic of Korea (ROK). China, Japan, and Republic of Korea (ROK)are now aware of the importance of this issue to their surrounding waters and their country’s development. However,the poor implementation of marine governance gives rise to the unsatisfactory effect of marine plastic waste governance in the sea area. Based on the concept of blue economy and the data of plastic pollution in the Yellow Sea and East China Sea, this paper discusses the feasibility of establishing binding legal norms and policies to promote the progress of marine plastic waste treatment in China, Japan and Republic of Korea. By using research methods of text analysis and status survey, this paper analyzes the differences and common demands of China, Japan and Republic of Korea for marine plastic pollution control. It is concluded that three countries have common demands in the management of the whole life cycle of marine plastic pollution, the establishment of flexible legal instruments, and the participation of stakeholders. Finally, through the case experience of the blue cycle model of marine plastic waste in Taizhou, Zhejiang Province, China, this paper proposes that this model can also be used in the management of marine plastic waste in China, Japan and Republic of Korea. Three countries can gradually promote the cooperation of marine plastic waste laws and regulations by starting with the treatment of fishery plastic waste, and innovate the blue cycle model, so as to finally promote the conclusion of the regional marine waste treatment agreement.